POKER: A new point kernel 3D radiation field characterization code with stratified and deep shielding capabilities - Chen, Junyi; Li, Ruihan; Chen, Yujia; Cao, Chenghao; Liang, Jingang (Nuclear engineering and technology, 2025)
Shielding calculations are essential for ensuring radiation protection and the safety of nuclear facilities. This paper presents POKER (POint KERnel shielding analysis code), a new 3D gamma shielding tool developed with the point kernel algorithm as its core computational framework. The code employs the Constructive Solid Geometry (CSG) method to efficiently model complex geometries. For shielding calculations, POKER integrates methods such as the GP fitting technique and Kalos’s correlations to derive single- and multi-layer buildup factors. For more intricate shielding scenarios, advanced formulas like the Broder formula and the Lin & Jiang formula are applied. Additionally, the code addresses deep penetration issues up to 100 mean free paths (MFPs), as demonstrated through verification. Photon cross-section data for attenuation coefficients are sourced from authoritative libraries to ensure accurate predictions. Comprehensive validation and verification have been conducted using benchmark problems from existing literature and the SINBAD database. POKER has been tested by calculating buildup factors (BUFs), multi-layer buildup factors (MLBUFs), and gamma dose rates at shield boundaries, with results compared against standard databases and experimental data. The validation results confirm POKER’s accuracy in handling single-layer, multi-layer, and deep penetration shielding scenarios. The code is developed using a modern programming framework and is compatible with cross-platform compilation and usage.